2017
DOI: 10.1002/ase.1758
|View full text |Cite
|
Sign up to set email alerts
|

What do medical students learn from dissection?

Abstract: Dissection has long been the accepted method for teaching anatomy to medical students. More recently, some educators have suggested that easier, cheaper, alternative methods are just as effective. But what do the students think? This paper aimed to identify what undergraduate medical students learn, how they cope, and what effects participating in dissection has on them as individuals. A cohort of 267 second year medical students at Otago Medical School were invited to complete three online surveys; before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 57 publications
4
85
0
2
Order By: Relevance
“…Although anatomical education has been undergoing reform in the medical profession, researchers have advocated that cadaveric dissection is the core method of teaching medical students as a foundation for developing clinical skills (Ghosh, ). Through dissection, most medical students have indicated positive effects on their learning (Flack and Nicholson, ). Similar to other Western countries, Taiwan’s medical education reform was implemented in 2000 (Chou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although anatomical education has been undergoing reform in the medical profession, researchers have advocated that cadaveric dissection is the core method of teaching medical students as a foundation for developing clinical skills (Ghosh, ). Through dissection, most medical students have indicated positive effects on their learning (Flack and Nicholson, ). Similar to other Western countries, Taiwan’s medical education reform was implemented in 2000 (Chou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being a useful tool to learn anatomy, it improves the students’ spatial reasoning skills and helps them relate structures to their images as they are usually represented. Dissection also promotes self‐reflection and integration of the cognitive and affective skills required for medical practice (Rizzolo and Stewart, ; Ahmed et al, ), and it is a useful tool to encourage teamwork, professional development and leadership among the students (Pawlina et al, ; Robbins et al, ; Talarico, ; Flack and Nicholson, ). Some have argued it constitutes the foundation of formal anatomy teaching (Rizzolo and Stewart, ; Lee et al, ; Somanath et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Students also generally support the idea of improving anatomy laboratory experiences. In a recently published survey by Flack and Nicholson (), it was found that medical students agree gross anatomy laboratory is a positive learning experience in preparing them for practicing medicine. This finding is also widely reinforced by other previous studies from the literature (Lempp, ; Azer and Eizenberg, ), as well as this report, as most students reported benefits from dissection laboratory (70% traditional; 72% sequential).…”
Section: Discussionmentioning
confidence: 99%
“…Manning et al () introduce the idea that cadaver dissections could be used to educate medical students on the suturing techniques required for their third‐year rotations. Anatomy laboratory also assists students in gaining a deeper understanding of human morbidity and mortality, and it allows the students to reflect on life and death (Aziz et al, ; Topp, ; Cho and Hwang, ; Flack and Nicholson, ). Additionally, it promotes professionalism, teamwork, and confidence in anatomical dissection (Escobar‐Poni and Poni, ; Spandorfer et al, ).…”
Section: Discussionmentioning
confidence: 99%